Why are the returns to education higher for entrepreneurs than for employees? - Justin van der Sluis; C. Mirjam van Praag; Arjen van Witteloostuijn (Institute for the Study of Labor (IZA), 2007)
We compare the returns to education (RTE) for entrepreneurs and employees, based on 19 waves of the NLSY database. By using instrumental variable techniques (IV) and taking account of selectivity, we find that the RTE are significantly higher for entrepreneurs than for employees (18.3 percent and 9.9 percent, respectively). We perform various analyses in an attempt to explain the difference. We find (indirect) support for the argument that the higher RTE for entrepreneurs is due to fewer (organizational) constraints faced by entrepreneurs when optimizing the profitable employment of their education.
Keywords: 330; Entrepreneurship; self-employment; returns to education employment; Bildungsertrag; Unternehmer; Selbstständige; Arbeitskräfte; Vergleich; Niederlande